Meyers' dynamic radiology of the abdomen normal and pathologic anatomy - Meyers, Morton A. (Springer, 2011)
The long-anticipated Sixth Edition of Morton Meyers? classic text, Dynamic Radiology of the Abdomen, is more than a revision. While holding to the fundamental theme of previous editions, the Sixth Edition is a new and updated presentation of a book that first introduced a systematic application of anatomic and dynamic principles to the practical understanding and diagnosis of intraabdominal diseases 34 years ago. The authorship of this revised text has been enlarged by the addition of two international authorities on intraabdominal disease processes?Chusilp Charnsangavej and Michael Oliphant. The insights introduced by Morton Meyers in the first edition and developed over subsequent editions have ensured the critical position of the radiologist in establishing the diagnosis and clearly established the dynamics and pathways of spread and localization of intraperitoneal infections and malignancies, among other things. The Sixth Edition builds upon this by broadening a vision to encompass global anatomic continuity throughout the abdomen and pelvis. New chapters detail the pattern of lymphatic spread of cancer from primary organs in the abdomen and pelvis Includes new information on the unifying concept of the subperitoneal space of the abdomen and pelvis for clinical applications Over 680 new and updated images and illustrations.